Impact of resveratrol-loaded liposomal nanocarriers on heat-stressed broiler chickens: Effects on performance, sirtuin expression, oxidative stress regulators, and muscle building factors - Kishawy, Asmaa T. Y.; Ibrahim, Doaa; Roushdy, Elshimaa M.; Moustafa, Amira; Eldemery, Fatma; Hussein, Elham M.; Hassan, Fardos A. M.; Elazab, Sara T.; Elabbasy, Mohamed Tharwat; Kanwal, Raheela; Kamel, Walid M.; Atteya, Mohamed R.; et al. (Frontiers in Veterinary Science, 2023)
Climate change is considered the core source of heat stress (HS) problems that particularly threats broilers chickens. Owing to unique properties of extracted polyphenols, resveratrol loaded liposomal nanoparticles (Resv-Lipo NPs) were first explored for alleviating harmful effect of HS. The dietary role of Resv-Lipo NPs in HS birds was investigated on their growth performance, antioxidative potential, and expression of heat shock proteins, sirtuins, antioxidant, immune and muscle building related genes. A total of 250-day-old Ross 308 broiler chickens were allocated into five experimental groups (5 replicates/group, 10 birds/replicate) as follows: control group; fed basal diet and reared in thermoneutral condition and other three HS groups which fed basal diet and supplemented with Resv-Lipo NPs I, II and III at the levels of 0, 50, 100, 150 mg/kg diet, respectively. The results indicated that Resv-Lipo NPs supplementation alleviated the retarded growth rate noticed in HS group. The highest body gain and most improved FCR were observed in Resv-Lipo NPs III group. Post HS exposure, the reduction in lipids profile and restoration of kidney and liver functions were detected in groups received Resv-Lipo NPs especially at higher levels when compared with HS group. The elevated corticosterone, T3 and T4 hormones levels in HS group were returned to normal ones in Resv-Lipo NPs III. Additionally, HS groups supplemented with Resv-Lipo NPs had improved serum and muscles antioxidant biomarkers. The upregulation of muscles and intestinal antioxidant-related genes (SOD, CAT, GSH-PX, NR-f2 and HO-1) and muscle building genes (myostatin, MyoD, and m TOR) was detected with increasing the level of Resv-Lipo NPs. Heat stress upregulated the heat shock proteins (HSP) 70 and 90 genes expression that restored to normal levels in HS+Resv-Lipo NPs III. Also, the expression of sirtuins (SIRT) 1, 3 and 7 genes were increased in liver of HS groups received Resv-Lipo NPs groups in dose dependent manner. Notably, upregulation of proinflammatory cytokines in HS group was restored in HS groups received Resv-Lipo NPs. Supplementation of Resv-Lipo NPs can recover the injurious impact of HS and consequently restore better broilers performance.